Labor Induction at 39 Weeks in Low-Risk Term Pregnancies and Risk of Perinatal Death [A263]. (May 2022) - Abenhaim, Haim A.; Czuzoj-Shulman, Nicholas; Benjamin, Alice; Spence, Andrea
Abstract : INTRODUCTION: Induction of labor (IOL) at 39 weeks has been associated with decreased risk of cesarean delivery. The study objective was to evaluate the effect of IOL at 39 weeks on perinatal death in low-risk pregnancies. METHODS: We used the National Center for Health Statistics Linked Birth/Infant Deaths data from 2013 to 2017 to carry out a propensity score matched cohort study to test the influence of IOL at 39 weeks on risk of stillbirth and infant death. Low-risk singleton pregnancies with a live fetus at 39 weeks with no known congenital malformations who underwent an IOL were matched with comparable pregnancies that were not induced at 39 weeks and that delivered no later than 42 weeks. RESULTS: From >20 million births, 825, 323 (4%) low-risk pregnancies that were induced at 39 weeks were propensity score matched (5:1 ratio) to a comparable group of pregnancies that were not induced at 39 weeks. Compared to pregnancies that were not induced at 39 weeks, IOL at 39 weeks was associated with increased risk of perinatal death (10.8 versus 5.8/10, 000; OR, 3.83.5–4.2; P <.0001), which consisted of a decreased risk of stillbirth (0 versus 0.7/10, 000) and an increased risk of infant death (10.8 versus 5.1/10, 000; OR, 4.2; 95% CI, 3.8–4.6; P <.0001). Among live-born infants, the risk of sudden infant death syndrome was more common among pregnancies induced at 39 weeks (OR, 4.3; 95% CI, 3.6–5.2; P <.0001). CONCLUSION: IOL at 39 weeks in low-risk singleton pregnancies is associated with an increased risk of perinatal death. While this may not have a material effect on risk to an individual patient, adoption of widespread practices of inducing low-risk pregnancies at 39 weeks may lead to increases in perinatal deaths on a population level.